LANGUAGE INTERFERENCE IN SENIOR HIGH SCHOOL STUDENTS’ WRITINGS (RETAIN, 2015)
ABSTRACT Language interference is believed to be a serious obstacle that interferes the students’ writings. Some studies have proved that students’ first language has interfered students’ writings. Therefore, it causes errors which make students’ writings are hard to understand. This study reports the errors in students’ writings as a result of first language interference and how the teacher attempts to reduce the interference. It is a qualitative content analysis which analyses 20 students’ writings of SMAN 1 GedanganSidoarjo and includes classroom observation. The results of this study revealed that 20 students’ writings are interfered by their first language that caused errors occur in students’ writings. This study also reports that the teacher usederror feedback as an attempt to reduce the interference. Observation on how the teacher attempts to reduce the interference shows that the teacher has successfully made the students reduce the errors as result of first language interference in their writings by themselves. Key words:Language Interference, Error, Teacher’s attempts, Students’ writings ABSTRAK PencampuranBahasadipercayaisebagaimasalah yang sangatseriuskarenadapatmencampurinahasadalambahasapenulisansiswa.Hal inijugamengakibatkantimbulnyakesalahan – kesalahan yang menyebabkantulisansiswasulitdipahami.Penelitianinimenelititentangkesalahan – kesalahan yang ada di dalamtulisansiswa yang disebabkanolehbahasasiswa yang mencampuritulisansiswa.Penilitianinijugamenelitibagaimanausaha guru untukmengurangipencampuranbahasatersebut yang mengakibatkantimbulnyakesalahan – kesalahanpadatulisansiswa.Penelitianinimenggunakanmetodequalitative content analysisdanclassroom observation.Hasildaripenelitianinimenunjukkanbahwa 20 tulisansiswatercampuriolehbahasamereka yang diindikasikandenganadanyakesalahan – kesalahanpadatulisansiswa. Selainitu, berdasarkanobservasidariusaha guru untukmengurangipercampuranbahasa, gurumenggunakanmetodeerror feedback yangtelahberhasilmembuatsiswamembetulkankesalahan – kesalahanmerekasendiri. Kata Kunci:pencampuranbahasa, kesalahan, usaha guru, tulisansiswa.